Some considerations on the potential contributions of intercultural social work... - Jan Fook (Social Work and Society)
Social work at global levels, and across international and intercultural divides, is probably more important now than ever before in our history. It may be that the very form our ideas about intercultural work take need to be re-examined in the light of recent global changes and uncertainties. In this short position paper I wish to offer some considerations about how we might approach the field of intercultural social work in order to gain new insights about how we practise at both local and global levels. For me, much of the promise of an intercultural social work (and for the purposes of this paper I see aspects of international social work in much the same light) lies in its focus on the way we categorise ourselves, our ideas and experiences in relation to others. The very notion of intercultural or international social work is based on assumptions about boundaries, differences, ways of differentiating and defining sets of experiences. Whether these are deemed "cultural" or "national" is of less importance. Once we are forced to examine these assumptions, about how and why we categorise ourselves in relation to other people in particular ways, the way is opened up for us to be much more critical about the bases of our own, often very deep-seated, thinking. This understanding, about how and why notions of "difference" operate in the way they do, can potentially open our understanding to all the other ways, besides cultural or national labelling, in which we categorise and create differences between ourselves and others. Intercultural social work, taken as a potential site for understanding the creation of difference then, has the potential to help us critically examine the bases of much of our practice in any setting, since most practice involves some kind of categorisation of phenomena.